Thyroid Papillary Microcarcinoma - Case report: Accidental Thyroid Nodule - From Diagnosis to Treatment: Microcarcinoma Papilar da Tiroideia - Relato de Caso: Nódulo Tiroideu Acidental - do Diagnóstico ao Tratamento - Jardim, Ana; Araújo, João Pedro; Montalvão, Pedro; Marinho, António; Amaro, Carla; Cruz, João; Ferreira, Mónica do Carmo; Saraiva, José (Gazeta Médica, 2018)
Thyroid nodules are very frequent on clinical daily basis, and ruling out malignancy, which may play the part in up to 4% a 6.5% of cases, represents their main clinical interest. Evaluating a thyroid nodule will depend on clinical as well as ultrasonography characteristics that will further determine which nodules should undergo fine needle aspiration – cytological result (1 out of 6 possibilities according to Bethesda system) will be the main determinant of therapeutic choice. This is a case report about the evaluation of an incidental thyroid nodule that is cytological indeterminate (follicular lesion of undetermined significance) which proved to be a papillary thyroid microcarcinoma.